The Influence of Organizational Culture on Performance through Employee Work Motivation - Anna Isnaini Wijayanti; Sri Hernawati; Zarah Puspitaningtyas (Health Notions, 2018)
Public health center is a the technical implementation unit of the health office of district are responsible for organizing health development in a working area. Sometimes the implementation of good performance can not run optimally with existing theory as happened at some health centers in Lumajang district. This research aimed to analyzed the influence of organizational culture on performance through employee worked motivation in the Worked Areas of Labruk Kidul Public Health Center, Gesang Public Health Center, and Sukodono Public Health Center. This type of research was a observational analytic with cross sectional design. Sample in this study were 167 employees, 55 employees from Labruk Kidul Public Health Center, 53 employees from Gesang Public Health Center, and 59 at Sukodono Public Health Center, selected using total sampling. Data were analyzed by Partial Least Square (PLS). Based on the test results, there was an influence of organizational culture on performance through employee worked motivation, with a t-value of 8.716 statistics (>1.96). The better organizational culture applied will increased employee worked motivation, so employee performance will also increased. To realize the excellent service oriented on improving the performance of employees, must be supported from all aspects of human resources, infrastructure, methods, environment both internal and external, and good management, so that existing facilities are expected to facilitate all aspects in the field of health in relation to public services which may h ave an impact on improving the performance of technical officers. Keywords: Organizational culture, Motivation, Performance